The stakeholder-communication continuum: An alternate approach to internal-and-external communications - Chen, Rita (My University, 2018)
The academic scholarship and professional literature to date have defined communications as existing in two groups: internal or external. Through a case-study examination of McMaster University and its alumni constituents, this paper suggests that communications (and by extension, stakeholder definition) can be viewed on a continuum. Dubbed the stakeholder-communication continuum, the proposed theory places internal and external communications on both ends of the spectrum, respectively; with stakeholder groups plotted along the continuum based on their relationship to the organization and each other. Depending on where the stakeholder group falls, communications can be internal, external, or a hybrid combination of internal/external. Using a triangulated research method in which a broad, representative survey was sent to alumni, in-depth interviews were conducted with university staff, and a content analysis of alumni-facing communications were conducted, the researcher examined the feasibility of the proposed stakeholder-communication continuum. What resulted is the revelation that McMaster staff view and treat their alumni as a key stakeholder that has both internal and external characteristics. As a result, communications to this constituent group differ from other stakeholders in both content and style. The paper concludes that a stakeholder-communication continuum may in fact be a plausible theory, and encourages further testing of the hypothesis.
Keywords: internal communications; external communications; two-way symmetrical communications; communications continuum; stakeholder identification; organization-public relationships; control mutuality; alumni; university